Filling the gap or taking the lead? Refugee led organisations in Uganda - Keluel Agook; Kuol Arou; Siham Ahmed; Joyeux Mugisho; Simon Marot Touloung; Hilde Refstie (Fennia: International Journal of Geography)
Authored by refugee leaders in Uganda for Fennia’s special issue on humanitarian localisation and accountability, this reflection asserts that our voices must be heard wherever displacement is analysed and policy is set. Nothing about us without us. Refugee-Led Organisations are not only first responders. We are educators, health promoters, peacebuilders and advocates. Our initiatives reach communities sooner, cost less and carries trust that international programmes rarely match. In this piece we argue that what we lack is not another training manual but the resources and authority that match with the responsibilities we already shoulder. This is needed if the humanitarian localisation agenda is to be anything more than a slogan.